Assessment of basis sets for density functional theory based calculations of core electron spectroscopies - Fouda, Adam E.A.; Besley, Nicholas A. (Springer, 2017)
The performance of gaussian basis sets for density functional theory based calculations of core electron spectroscopies is assessed. The convergence of core-electron binding energies and core-excitation energies using a range of basis sets, including split-valence, correlation consistent, polarisation consistent and individual gauge for localized orbitals basis sets is studied. For Δself-consistent field calculations of core-electron binding energies and core-excitation energies of first row elements, relatively small basis sets can accurately reproduce the values of much larger basis sets, with the IGLO basis sets performing particularly well. Calculations for the K-edge of second row elements are more challenging and of the smaller basis sets, pcSseg-2 has the best performance. For the correlation-consistent basis sets, inclusion of core-valence correlation functions is important, with the cc-pCVTZ basis set giving accurate results. Time-dependent density functional theory based calculations of core-excitation energies show less sensitivity to the basis set with relatively small basis sets, such as pcSseg-1 or pcSseg-2, reproducing the values for much larger basis sets accurately. In contrast, time-dependent density functional theory calculations of X-ray emission energies are highly dependent on the basis set, but the IGLO-II, IGLO-III and pcSseg-2 basis sets provide a good level of accuracy.